Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.2147/vhrm.s3985
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF-β on cardiac structural and electrical remodeling

Abstract: The type β transforming growth factors (TGF-βs) are involved in a number of human diseases, including heart failure and myocardial arrhythmias. In fact, during the last 20 years numerous studies have demonstrated that TGF-β affects the architecture of the heart under both normal and pathological conditions. Moreover, TGF-β signaling is currently under investigation, with the aim of discovering potential therapeutic roles in human disease. In contrast, only few studies have investigated whether TGF-β affects el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 93 publications
0
6
0
1
Order By: Relevance
“…One of its gene targets is the mothers against decapentaplegic homolog 4 ( SMAD4 ) which upon binding with DACH1 can result in repression of TGFβ signaling and TGFβ-induced apoptosis [23] . In this regard, increased TGFβ1 activity has been implicated in heart and vascular development, hypertension and progressive myocardial fibrosis [24] , [25] . In a recent proof-of-concept analysis, researchers merged co-expression and interaction networks and detected/inferred novel networks to explain the frequent but not invariable coexistence of diabetes and other dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…One of its gene targets is the mothers against decapentaplegic homolog 4 ( SMAD4 ) which upon binding with DACH1 can result in repression of TGFβ signaling and TGFβ-induced apoptosis [23] . In this regard, increased TGFβ1 activity has been implicated in heart and vascular development, hypertension and progressive myocardial fibrosis [24] , [25] . In a recent proof-of-concept analysis, researchers merged co-expression and interaction networks and detected/inferred novel networks to explain the frequent but not invariable coexistence of diabetes and other dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial fibrogenesis is induced by TGF-b1 (13,15,(24)(25)(26). To test whether TGF-b1 is increased in deceased COVID-19 patients, we measured TGF-b1 mRNA levels by quantitative RT-PCR in left ventricular tissue taken from patients with COVID-19.…”
Section: Fibrotic Markers Are Increased In Deceased Covid-19 Patientsmentioning
confidence: 99%
“…TGF-b1 binding to its receptor leads to phosphorylation of intracellular SMAD3, which upregulates profibrotic genes (15,24,25), resulting in increased expression of collagens or fibronectin. Although altered levels of SMAD3 RNA would not necessarily equate to altered SMAD3 activity, it has been shown in a variety of tissues that TGF-b1-induced upregulation of SMAD3 can be an important inducer of reactive oxygen species (ROS) via upregulation of NADPH oxidases II and IV (NOX2/NOX4) (25)(26)(27)(28)(29).…”
Section: Fibrotic Markers Are Increased In Deceased Covid-19 Patientsmentioning
confidence: 99%
“…Inflammation and oxidative stress have been found to be responsible of many molecular mechanisms of CD including activation of immune cells such as macrophages, T and B cells, neutrophils and inflammatory cytokines (IL-6, TNF-α). These cytokines and activated immune cells could affect the contractility and electrical myocytes stability inducing fibroblast activation and cellular fibrosis [24][25][26]. These atrial changes provide reentrant arrhythmias confirmed clinically and electrocardiogram [27].…”
Section: Discussionmentioning
confidence: 83%